BETWEEN ?-CLOSED SETS AND g?-CLOSED SETS - O. Ravi, V. John Rajadurai (Mathematical Statistician and Engineering Applications, 2022)
In this paper, further study is carried out using the established generalized classes of ??. Apart from this, some new generalizations of ?-open sets are introduced and investigated. Also, using the generalized subsets of ?? , a new decomposition of ?-continuity in topological spaces is obtained